Materials to Enable Future OLED Display Evolution. (18th January 2023) - Engelhart, Jens; Stolz, Sebastian; Ganss, Stephanie; Ricks, Michele
Abstract: Experimental and theoretic approaches will allow for new understandings that are essential to develop OLED materials that enable next‐generation displays.